2012
DOI: 10.1016/j.addbeh.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of impulsivity among heavy drinkers, smokers, and heavy drinking smokers: Singular and combined effects

Abstract: Alcohol use and cigarette smoking commonly co-occur. The role impulsivity may play as a common underlying mechanism in alcohol use and cigarette smoking is of particular interest due to emerging evidence of it being a critical component across multiple forms of addiction. Impulsivity can be examined through several constructs including, risky decision-making, response inhibition, and delay reward discounting. Impulsivity and each of these specific constructs play significant roles in the initiation of drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 36 publications
9
26
0
Order By: Relevance
“…On one hand, when heavy smoking was present, dual-substance use was associated with greater discounting than cigarette smoking alone. This observation indicates an additive effect of dual-substance use with regard to cigarette smoking populations, consistent with the findings of García-Rodríguez et al (2013) and Moallem and Ray (2012). On the other hand, dual-substance use of alcohol and cocaine was not associated with significantly different rates of discounting than the mono use of any substance.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…On one hand, when heavy smoking was present, dual-substance use was associated with greater discounting than cigarette smoking alone. This observation indicates an additive effect of dual-substance use with regard to cigarette smoking populations, consistent with the findings of García-Rodríguez et al (2013) and Moallem and Ray (2012). On the other hand, dual-substance use of alcohol and cocaine was not associated with significantly different rates of discounting than the mono use of any substance.…”
Section: Resultssupporting
confidence: 87%
“…Specifically, Moallem and Ray (2012) found additive discounting effects of smoking and alcohol use whereas García-Rodríguez et al (2013) and Businelle et al (2010) did not find an increase in discounting effects in combined smoking and cocaine dependence or combined smoking and substance dependence, respectively. Moreover, Businelle's design allowed for all substance dependencies other than nicotine dependence for inclusion in a “substance use disorder’ group.…”
Section: Introductionmentioning
confidence: 87%
“…Seven studies reported results that varied according to gender and cigarette consumption levels, with stronger associations of time-discounting with smoking among men and more dependent smokers 57–63 . Seven studies found that people with other substance use or mental health problems had stronger associations of smoking and time-discounting, including cocaine-dependent smokers, 64 those with depressive symptoms, 65 heavy drinkers, 66 obese persons 67 and individuals with gambling problems, 68 compared with smokers without these symptoms 69–73 …”
Section: Resultsmentioning
confidence: 99%
“…One study found an association in African Americans but not European Americans [29], and another study found that discounting predicted drinking in females but not males [30]. In studies of cigarette smokers, discounting was also related to severity of nicotine dependence [3135], but see [36], and individuals who were both drinkers and smokers discounted more than drinkers or smokers only [37]. Similarly, both cocaine- and opiate-dependent individuals discounted more than healthy controls [21, 3840], although see [41], and delay discounting was greater for early or intermediate onset opiate dependence compared with late-onset [42].…”
Section: Studies Comparing Drug Users and Non-usersmentioning
confidence: 99%